Tensile properties of graphene epoxy nanocomposite - Raja N Othman; Abdul. H. Zainudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
In this research, tensile test was conducted to reveal the notable enhancement of Young Modulus and tensile stress composites. Epoxy resin is a cross-linked polymer, thus it has major influence on the properties of polymers generally in hardness, strength, stiffness, brittleness, and better dimensional stability. Epoxy resin plays many roles in industry especially in adhesion process in automotive and aerospace composites. Discovered in 2004, graphene has revealed that it has tremendous mechanical properties and thermal properties. On top of that, addition of graphene to epoxy can lead to innovate in various adhesion industry and structural materials. In this project, an experiment was conducted in various phases which varying with graphene loading ratio, stirring speed, and stirring time. Outcome from this experiment showed that 1.0% of graphene loading with 500 rpm stirring speed and 30 minutes stirring time shows the optimum condition to enhance the measured properties. The enhancement showed are 53.03 % of Young Modulus and 51.19 % for tensile test result compared to the preliminary result. This study clearly stated the enhancement of mechanical properties of epoxy composites by merely adding 1 wt.% graphene.